Customized spatial niches for synthetic microbial consortia - Gao, Hao; Jiang, Wankui; Zhang, Wenming; Jiang, Min; Xin, Fengxue (Trends in biotechnology (Regular ed.), 2023)
The construction of synthetic microbial consortia has been considered a new frontier. However, maintaining artificial microbial communities remains challenging because the dominant strain eventually outcompetes the others. Inspired by natural ecosystems, one promising approach to assemble stable consortia is to construct spatial niches partitioning subpopulations and overlapping abiotic requirements.